Mercantilização da educação e docência em instituições de ensino superior privado - Nonnenmacher, Solange (2008)
The theme of this research came from the author s observations on a current and general trend of encompassing the business culture that is seen in the form of trading concepts and actions, in superior teaching institutions, a process that occurs because of the increasing private condition of this teaching level. This fact alludes to a question: What implications do the institutional practices, identified with the market culture, bring to the teaching process in the private superior institutions? The investigation proposes to unveil and to analyze the view of some teachers of the private superior institutions on the process of teaching which they face in order to establish relations among their reported performances of teaching and the global contexts with the theoretical and practical references about this theme. To achieve this goal, it was aimed to get some support in the literature that approaches the matter of the mercantile status of education, the questions that the current university faces, the historical tendency of making the Brazilian education and the private superior teaching activities. Considering the nature of this theme and the objectives of this study, it was chosen an approach to the qualitative research in which it was studied, in an interview, twelve professors professionally graduated in different areas of knowledge, who work in three private superior institutions, classified according to their types. The analysis and the interpretation of the professors testimonies, under the optics of the theoretical reference built for this research, points out an exaggerated trend to transform the market questions, which belongs to the teaching in the superior education, including the professor s profile, the working conditions, the teaching performances, the relations of these institutions with the community and the character of the formation offered by them where the connections of the local processes are evident in the global context to be discussed. The research, although is limited in its geography and its number of participant subjects, might contribute in new and larger studies that aim to discuss on the review and the critical analysis of the private superior teaching in Rio Grande do Sul state in its relations with the society and in its function as a social institution.